Relationship Between Parenting Styles and Psychological Well-Being Among Adolescents : An Analysis of Authoritative, Authoritarian, Permissive, and Uninvolved Parenting - Sashifa Nissa Tiara; Dian Pitaloka Priasmoro; Riki Ristanto (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Parenting style is a critical determinant of adolescent psychological well-being, yet evidence from semi-rural Indonesian settings remains limited. This study examined the relationship between parenting style and psychological well-being among adolescents at SMP Negeri 1 Pacet. Methods: A cross-sectional correlational design was employed involving 192 students aged 14–16 years. Parenting style was measured using the Parenting Style Four Factor Questionnaire (PS-FFQ), and psychological well-being was assessed using the Ryff Psychological Well-Being Scale (18 items). Data were analyzed using the Chi-Square test to determine the association between the variables. Results: Authoritative parenting was the dominant style (65.1%), while authoritarian (16.7%), permissive (10.9%), and uninvolved (7.3%) were less prevalent. Most adolescents demonstrated high psychological well-being (63.0%), followed by low (18.8%) and moderate (18.2%) levels. Chi-Square analysis revealed a highly significant relationship between parenting style and psychological well-being (χ² = 180.999; df = 6; p < 0.001). Adolescents with authoritative parents consistently showed higher psychological well-being, while other parenting styles were associated with lower levels. Conclusions: Parenting style significantly influences adolescent psychological well-being, with authoritative parenting serving as a strong protective factor. These findings highlight the importance of supportive, structured, and communicative parenting practices in promoting adolescent emotional health. Interventions aimed at strengthening positive parenting and enhancing family–school collaboration may improve adolescent well-being in semi-rural communities.